Sauna is not a bath : A study of Finnish loanwords in English through the historical lens of Finnish immigrants in North America - Latostenmaa, Matias (My University, 2024)
In this thesis, I study Finnish loanwords in English to understand what they reveal about the interactions of the Finns and the English-speaking Americans. I chose to study specifically the Finns in North America because the largest emigration waves from Finland were to America so there is plenty of material on this subject. Furthermore, there are still Finnish speaking communities in these areas. As a material, I use the words marked with Finnish origin in the Oxford English Dictionary and the loanwords gathered by Olga Timofeeva in their study The Wor(l)ds of Kalevala (2013). These lists differ from each other quite significantly, so I cross-reference them to form my own list of loanwords for this study. As a methodology to contrast the Finnish and American cultures I use the ethnography of communication, which gives deeper insight into the cultural norms and expectations for communication. There are many reasons behind the lack of words loaned from Finnish. These range from the differences between conversational cultures of Finland and America to the secluded locations of the Finnish settlements. While my main focus is on the past since most of the loans date back to 19th and early 20th century, I also investigate why there are not many loans from later dates. The main reasons for this are the prevalence of English in international corporations and the eagerness of Finns to learn languages. Further research into how different cross-cultural interactions affect the loaning of words is needed.
Keywords: loanwords, ethnography of communication, Gricean maxims, Finnish, English